Emerging applications for magnesium alloy powders. (September 2014) - Tandon, Rajiv; Madan, Deepak
<x content-type="archive" xml:space="preserve">Abstract</x> Efforts to reduce fuel consumption have led to renewed interest in the use of magnesium alloys for lightweighting of transportation structures. Powder metallurgy offers a processing route to target unique compositions, unique microstructures and high performance in magnesium alloys. Recent advances in the production, qualification, and characterisation of gas atomised AZ91E, WE43 and Elektron21 alloy powders are highlighted. The structure of the atomised powder was investigated using TEM. Fulfilling the potential of these magnesium alloys powders for emerging applications involves establishing compatibility with viable consolidation processes such as cold spray, laser assisted deposition, forging and extrusion. Preliminary results in this endeavour are reported.